2007
DOI: 10.1007/s00468-007-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

Linking multiple-level tree traits with biomass accumulation in native tree species used for reforestation in Panama

Abstract: To improve establishment yield and carbon accumulation during reforestation, analyses of species adaptations to local environments are needed. Here we measured, at the individual scale, links between biomass accumulation and multiple-level tree traits: biomass partitioning, crown morphology and leaf physiology. The study was carried out on one-and three-year-old individuals of five tropical tree species assigned to pioneer (P) or nonpioneer (NP) functional groups. Among the species, Cedrela odorata, Luehea see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
1
21
0
1
Order By: Relevance
“…This particular difference in leaf morphology between functional types is critical since it provides contrasting nitrogen and water-use efficiencies and different leaf life spans (Terwilliger et al 2001;Onoda et al 2004). In a parallel study conducted in the same experimental site we found a positive relationship between SLA and leaf photosynthetic nitrogen use efficiency (PNUE) (Delagrange et al 2008) and Kitajima (1994) and Walters et al (1993), among others, have reported higher photosynthetic rates and SLA values for pioneer species than for non-pioneers when growing under high light conditions. SLA is known to well predict photosynthetic capacity under high light conditions and particularly at The main factors included in the analyses were the functional type (pioneer or non pioneer) and the species nested under these groups Trees (2008) 22:585-596 591 fertile sites (Craven et al 2007).…”
Section: Structural and Allocational Differences Among Tropical Tree mentioning
confidence: 50%
See 1 more Smart Citation
“…This particular difference in leaf morphology between functional types is critical since it provides contrasting nitrogen and water-use efficiencies and different leaf life spans (Terwilliger et al 2001;Onoda et al 2004). In a parallel study conducted in the same experimental site we found a positive relationship between SLA and leaf photosynthetic nitrogen use efficiency (PNUE) (Delagrange et al 2008) and Kitajima (1994) and Walters et al (1993), among others, have reported higher photosynthetic rates and SLA values for pioneer species than for non-pioneers when growing under high light conditions. SLA is known to well predict photosynthetic capacity under high light conditions and particularly at The main factors included in the analyses were the functional type (pioneer or non pioneer) and the species nested under these groups Trees (2008) 22:585-596 591 fertile sites (Craven et al 2007).…”
Section: Structural and Allocational Differences Among Tropical Tree mentioning
confidence: 50%
“…All leaves from the saplings were harvested and dried to provide total leaf biomass. We used specific leaf area (SLA) calculated from another study (Delagrange et al 2008) to scale up biomass of leaves to total leaf area per tree. SLA values were obtained from fifteen to twenty-five leaves per species where the leaf area had been measured with a leaf area meter (Li-Cor 3100) before being dried and weighed.…”
Section: Allometric and Morphological Measurementsmentioning
confidence: 99%
“…In fact, shrubby legumes are widely distributed in regions with a Mediterranean-type climate (Del Pozo and Aronson 2000;Rodrı´guez-Echeverrı´a et al 2003). Actinorhizal species also have been considered as pioneer species in pasture ecosystems (Croat 1978;Delagrange et al 2007). In the arid valley, there are other actinorhizal plants (C. nepalensis and Myrica rubra).…”
Section: Discussionmentioning
confidence: 99%
“…However, chosen tree species are often exotics (frequently Eucalyptus and Pinus spp.) which have desired traits of fast growth, high yield, known site preference and high reproduction [49]. Neither the ecological nor genetic impacts of these approaches have been well studied, nor have genetic monitoring programs been established to watch for impacts on native populations.…”
Section: Carbon Sequestrationmentioning
confidence: 99%